Too Few Women in Top Posts in the Big Banks and Insurance Companies - Elke Holst; Anne-Katrin Stahn (Weekly Report, 2007)
The share of women on the supervisory boards (Aufsichts- und Verwaltungsräte) of the big banks, savings banks and insurance companies in Germany is low. In the banking sector it is 15% and in insurance 11%. That women are to be found on most supervisory or administrative boards is mainly because they are workers representation delegates. Posts on management boards (Vorstände) in the big insurance companies and banks, on the other hand, are, like those in the other big companies, firmly in male hands. Only 2.5% are occupied by women. So there is a huge gap between the high share of women employed in the financial sector as a whole (54%) and their presence on the top decision-making bodies.
Keywords: J16; J4; J5; 330; Women; finance; supervisory boards